2005
DOI: 10.1103/physrevb.72.045319
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb blockade in two-island systems with highly conductive junctions

Abstract: We report measurements on single-electron pumps, consisting of two metallic islands formed by three tunnel junctions in series. We focus on the linear-response conductance as a function of gate voltage and temperature of three samples with varying system parameters. In all cases, strong quantum fluctuation phenomena are observed by a log (kBT /(2Eco)) reduction of the maximal conductance, where Eco measures the coupling strength between the islands. The samples display a rich phenomenology, culminating in a no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Serial arrays of islands 13,14,15,16,17,18,19,20,21 have been put forward for metrological purposes: for primary thermometry 16 and, operated as electron pumps, as a standard for both current and capacitance. 17,18,19,20 For each cycle of periodically changing the gate voltages one electron is transfered through the system.…”
Section: Introductionmentioning
confidence: 99%
“…Serial arrays of islands 13,14,15,16,17,18,19,20,21 have been put forward for metrological purposes: for primary thermometry 16 and, operated as electron pumps, as a standard for both current and capacitance. 17,18,19,20 For each cycle of periodically changing the gate voltages one electron is transfered through the system.…”
Section: Introductionmentioning
confidence: 99%
“…Thus energy-dependence of the barriers is not necessary. The involved technology is within nowadays reach [62,63,64,45,41,47] and could readily be tested in an experiment. This proposal contributes to the field of interaction-induced thermoelectric properties [59,60] and the control of thermal flows [71,72] in lowdimensional metallic conductors.…”
Section: Discussionmentioning
confidence: 99%
“…Consider an array of three tunnel junctions forming two islands [61,62,63,64], as sketched in Fig. 1.2.…”
Section: Two Coulomb Islands In Seriesmentioning
confidence: 99%
“…In this section, we focus on the two-metallic island system [18,28] and calculate average electron numbers of the system by the Monte Carlo method. Limbach et al [18] reported the experimental results of two-metallic island systems, usually called the single electron-pump (the SEP), which can be represented by the circuit diagram in Fig. 2.…”
Section: Two-island Systemmentioning
confidence: 99%
“…In addition, one can apply the path integral Monte Carlo simulation [10,11,12,13] to study the systems as the SET without the restriction of coupling parameters and temperature as perturbation theory [14,15,16] and semiclassical approximation [8,17], respectively. However, since the complexity of the single-electron tunneling devices depends on the number of the island, it is still unclear whether the theoretical calculation would agree with more complex experiments than that of the SET, i.e., the systems consist of many islands [18,19,20].…”
Section: Introductionmentioning
confidence: 99%